A total systems study on Singularity - Celiz, Mary Angelique; Gutierrez, Ria Mae; Ngo, John William K.; Ramos, April Rose; Señires, Luis Gabriel D. (College of Engineering, University of the Philippines Diliman, 2014)
In a decade, the Information Technology and Business Process Management (IT-BPM) in the Philippines has grown at an annual rate of 30%. Computerization of processes has become very appealing for providing an easier means of gathering, handling and processing information. Moreover, BPM is largely in-demand because of its promised boosts in the efficiency and effectiveness of an organization's processes. Having been founded in 2012, Singularity Solutions, Inc. has been active in pursuing excellence in getting clients and bringing the best services as an official Google Apps reseller and in-house developer. Singularity was initially the IT arm of the Ramcar Group of Companies. Recently, and consequently to this study, Singularity aims to be independent of their partnership with Google Enterprise. And with this, they want to perform at par with what they have been doing while in partnership. The study mapped out the ideal process of the company and analyzed the current structure of the company, through data obtained of the company's performance for the past 6 months. Methods engineering, gap analysis and financial analysis were done to investigate potential problems. It has been found out that the company has generated 300% in target sales last year. This triggered the management to further increase the target sales by 100% more for 2014. By gap analysis, it has shown that doubling the sales given the same productivity would result to an employee overutilization of 106%. It was also discovered through financial analysis that the company lacked proper monitoring when it came to financials, since some of the expenses were not accounted and undeclared for the past deployments, resulting to abnormally inflated profits. The study recommended a flowchart guide to be used by the telesales of the Business Development to help them increase the probability of turning potential leads to clients. Also, an account manager is created to help with the tracking and management of the client statuses. This would save time and effort and help them increase their productivity. Additionally, a spreadsheet template for the financial documentation is recommended which can be filtered by client category and by cost category. The cost categories were reduced to five to be able to minimize complications due to over classification. Lastly, the existence of a resource request form is recommended for transparency in giving the Finance Operations Department information on how many licenses have been purchased. This can aid in properly allocating the said expenses in the financial documentation, to prevent the reported inflated profits. As an added measure, it was also recommended to record the actual man-hours during the deployment phase for each contract, to obtain an intensive documentation on labor costs. Also, it is advised that the standard project plan, as documented in the ideal process of the company, should be immediately implemented, to better monitor future project statuses. All these recommendations are laid out for the company's further improvement, and to aid in their goal of increasing to 100% more target sales at the end of 2014.